2021
DOI: 10.1136/heartjnl-2021-319110
|View full text |Cite
|
Sign up to set email alerts
|

Association between ibrutinib treatment and hypertension

Abstract: BackgroundIbrutinib is a tyrosine kinase inhibitor most commonly associated with atrial fibrillation. However, additional cardiotoxicities have been identified, including accelerated hypertension. The incidence and risk factors of new or worsening hypertension following ibrutinib treatment are not as well known.MethodsWe conducted a retrospective study of 144 patients diagnosed with B cell malignancies treated with ibrutinib (n=93) versus conventional chemoimmunotherapy (n=51) and evaluated their effects on bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…The above situations proved that HTN was not a robust signal. Several studies suggested that HTN is an adverse effect of ibrutinib [ 35 , 36 ]. The ibrutinib FDA label also indicated that in clinical trials of 1476 patients who received ibrutinib, HTN could occur in 19% of patients, and 8% of patients could experience grade 3 or higher HTN.…”
Section: Discussionmentioning
confidence: 99%
“…The above situations proved that HTN was not a robust signal. Several studies suggested that HTN is an adverse effect of ibrutinib [ 35 , 36 ]. The ibrutinib FDA label also indicated that in clinical trials of 1476 patients who received ibrutinib, HTN could occur in 19% of patients, and 8% of patients could experience grade 3 or higher HTN.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our model may have underestimated the toxicity of IB, as some real-world studies have reported that treatment withdrawal rates and adverse effects were signi cantly higher compared to clinical trial data [41,42]. Furthermore, for patients with a history of hepatitis, treatment with IB may also lead to the reactivation of hepatitis virus infection [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…This could in part explain a concerning report that over 60% of patients treated with ibrutinib, who were hypertensive at follow-up did not receive an increase or any additional BP medications. 269 The consensus statement by the International Cardio-Oncology Society is an example of progress made to better adapt and modify recommendations for management of hypertension whilst incorporating CVD risk, BP thresholds for withholding anticancer treatment, and consideration of abrupt treatment-related hypertensive changes which may trigger initiation or escalation of treatment. 222 However, there remain inconsistencies between various guidelines and recommendations for optimal assessment and pharmacological management of hypertension, and there is growing need for large-scale clinical trials to further guide optimal individualized cancer and therapy-specific treatment pathways.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%